IMPLEMENTASI JUAL BELI ONLINE DALAM PERSPEKTIF SYARI’AT ISLAM DI DESA PELAWAD-KECAMATAN CIRUAS-KABUPATEN SERANG - Rikil Amri; Aep Saepul Anwar (Teknik Mesin ,Universitas Pamulang Serang, 2024)
In the era of globalization, technology is growing so rapidly that gadgets have become a tool for online buying and selling activities. Nowadays there are lots of buying and selling transactions via cyberspace or the Internet, so that merchants and buyers do not have to meet and are limited by time and space. Online buying and selling is included in the muamalah aspect which is permitted by any principle, unless there are indications that it is prohibited, the terms and conditions of online buying and selling do not conflict with the rules or terms and conditions in the realm of Islam. Trading online will be haram if there are haram elements, such as gahar (fraud), usury, harm, lack of clarity, causing harm to other parties, coercion, or the goods being traded are not in accordance with the original, rather than halal things such as liquor, pork, carcasses, online gambling narcotics or slots and so on. The online buying and selling business contains many advantages and benefits from various aspects such as facilitating time efficiency. The aim of the PKM activity is to carry out socialization regarding online buying and selling commerce which is in line with religious law, and providing implementation materials for online buying and selling according to the perspective of the Islamic law. Islam, this is carried out as a simulation of online buying and selling in accordance with Islamic law. Stages of activities carried out by PKM colleagues. including:. 1) Chairman. and teammates hold discussions online or. face to face to discuss. theme of Devotion to. the Communities (PKM). Do. Survey to Pelawad Village, Ciruas District, Serang Regency and arrange permits and determine the location of the activity and time for implementation, 3) Discuss with the Head of Pelawad Village and local community leaders 4) Prepare activity equipment such as banners, as well as administrative readiness and health protocol equipment, 5) the entire team. Carry out dedication. Keywords: Implementation, Buying and Selling, Online, Islamic Perspective.